(untitled) (Journal on studies and research of academic knowledge, 2018)
This work deals with conflicts concerning Children and Adolescents, which due to their personal and emotional connotations, because the litigants are or have been family, we see the need to seek to affect children and / or adolescents involved as little as possible. To this end, a self-supporting method was considered, such as mediation, in order to preserve the relationship between the parties in order to reach an efficient solution. The objective was established: the application of a collaborative conflict resolution mechanism as more efficient to resolve conflicts derived from the family bond in comparison to an adversarial mechanism. This purpose was obtained from the bibliographic and legal review, also through interviews and statistical data from the Office of Mediation of the Judiciary and the Court of the 1st Instance of Childhood and Adolescence, 1st Turn, Secretariat No.1 of Encarnación. Research shows that the application of mediation is preferred in order to preserve the relationship in the types of cases mentioned, the amount of these completed by this means demonstrate their efficiency allowing the Judge to understand exclusively in cases that due to their complexity need a express judicial decision.